1995
DOI: 10.1002/mrm.1910340603
|View full text |Cite
|
Sign up to set email alerts
|

Imaging myocardial fiber architecture in vivo with magnetic resonance

Abstract: Methods are presented to image the fiber architecture of the human myocardium in vitro and in vivo. NMR images are obtained of the diffusion anisotropy tensor, indicative of local myofiber orientation. Studies of cardiac necropsy specimens demonstrate classic features of ventricular myoarchitecture including the continuous endocardial to epicardial variation of fiber helix angles (angles to the ventricular circumferential direction) of approximately +1.3 to -1.3 radians. Cross-fiber anisotropy is also observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
269
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(285 citation statements)
references
References 20 publications
12
269
1
1
Order By: Relevance
“…DTI has been successfully applied to the analysis and depiction of neuronal fibers in the living human brain (Mori and van Zijl, 2002). Furthermore, qualitative agreement between main diffusion directions and the fiber orientation in myocardium (Garrido et al, 1994;Reese et al, 1995;Scollan et al, 1998;Schmid et al, 2005) and skeletal muscle (Van Donkelaar et al, 1999;Napadow et al, 2001;Damon et al, 2002;Mori and van Zijl, 2002;Heemskerk et al, 2005) was observed.…”
mentioning
confidence: 89%
“…DTI has been successfully applied to the analysis and depiction of neuronal fibers in the living human brain (Mori and van Zijl, 2002). Furthermore, qualitative agreement between main diffusion directions and the fiber orientation in myocardium (Garrido et al, 1994;Reese et al, 1995;Scollan et al, 1998;Schmid et al, 2005) and skeletal muscle (Van Donkelaar et al, 1999;Napadow et al, 2001;Damon et al, 2002;Mori and van Zijl, 2002;Heemskerk et al, 2005) was observed.…”
mentioning
confidence: 89%
“…These include: (1) the use of the octahedral icon for each pixel (Reese et al, 1995); (2) color maps, where different intensities of the three colors indicate the size and the ADC in each of the three Cartesian directions (Makris et al, 1997); (3) rendered ellipsoids to visualize diffusion data in a slice, and (Pierpaoli et al, 1996); and (4) the use of lines to represent the in-plane component of the principal diffusion direction, along with a color-coded out-of-plane component ) (see Fig. 4).…”
Section: Quantitative Representation Of Diffusion Tensormentioning
confidence: 99%
“…Moreover, we have not taken into account the variance of both fiber and sheet direction at each site. At the present time, it is not possible to determine fiber and sheet anatomy in the beating heart, although diffusion MRI shows considerable promise (29). Thus measurements must be done in different hearts fixed at different filling pressures, a task that has not been undertaken in larger hearts.…”
Section: Limitationsmentioning
confidence: 99%